Retinal Vein Occlusion with COVID-19: A Case Report and Review of Literature. (16th March 2023) - O'Donovan, Charles; Vyas, Neel; Ghanchi, Faruque
ABSTRACT: Objectives: To provide a case report of Retinal Vein Occlusion (RVO) with COVID-19 infection. Case: A 15-year-old healthy male presented with blurring of vision, 2+ vitreous cells, retinal haemorrhages and dilated and tortuous retinal vessels in the left eye within 28 days of a positive COVID-19 reverse transcriptase polymerase chain reaction (RT-PCR) assay. He was diagnosed with left non-ischaemic CRVO, with a suspected aetiology of COVID-19. Discussion: A literature review found 12 reported cases of RVO associated with COVID-19. All but one patient was younger than 60, with a mean age of 42 years. Management varied, but in the majority (8/12), visual acuity (VA) improved with follow-up, and five (42%) had a final VA of 20/20 Conclusion: In the absence of other known aetiological factors, ophthalmologists should consider COVID-19 as a cause of RVO. The outcome can vary, but the majority can expect improvement in VA with time.